Simulasi Lampu Lalu Lintas Simpang Tiga Balikpapan Permai berbasis PLC OMRON CP1E-N30SDR-A - Riza Hadi Saputra; Ain Sahara; Melinda Greshela (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2019)
Today on the highway, especially on crossing roads, motor vehicle users are increasing, both motorbike and car drivers. Not only that, it can be seen from the number that has increased greatly every day. This situation requires the existence of a time setting, whose purpose is nothing but to reduce congestion to the risk of accidents. Therefore, in this study, a traffic light simulation is controlled by OMRON CP1E-N30SDR-A PLC. Traffic light simulation at the three intersections based on PLC OMRON CP1E-N30SDR-A has been made a traffic light control prototype to set the timing of traffic lights at the three intersections based on OMRON CP1E-N30SDR-A PLC. The method used for this research is observation, looking for references about sending data at traffic lights and can be processed on PLC systems. Observations were carried out directly at the place of data collection, namely at Simpang 3 Balikpapan Permai. Programming used to instruct traffic light simulations is to use a ladder diagram programming language created using CX-Programmer software. The purpose of this study is to make a traffic light system in the form of a simulation or prototype that has timing from intersection 3 of Balikpapan Permai. In traffic light simulations, timers are needed to synchronize between available intersections, namely 3 intersections. This is so that the vehicle that passes from one intersection where the traffic light conditions at that time is a green light, then the vehicle no longer waits at the next intersection. The signal is sent from one intersection to another as an indicator so that the intersection can automatically adjust the timing of traffic lights.